Synthesis of Fe(III) and Co(II) Thia-Containing Schiff Base Complex and Applications for Optical Chemosensor - Ershad, Sohrab; Sagathforoush, Lotf-Ali; Karim-Nezhad, Ghasem (Asian Journal of Chemistry, 2010)
A new optode membrane for the sensitive and selective determination of thiocyanate ion based on a change in absorption spectrum of a polymer film, is proposed. A membrane composed of plasticized poly vinyl chloride (PVC), Fe(III) and Co(II) Schiff-base complex as chromo-ionophore and hexadecyl trimethyl ammoniuom bromide (HDTMABr) as cationic additive was prepared. The influence of different plasticizers was studied for the sensitivity, linear range, selectivity of the membrane film. Satisfactory analytical sensing characteristics for determining thiocyanate ion were obtained in terms of the selectivity, reversibility and reproducibility with a good detecting range. The optical film based on Fe(III)- complex responds to thiocyanate ion reversibly over a wide dynamic range 1.0 × 10-7 to 1.0 × 10-3 M with fast response and recovery times. The optode membrane has been applied to determine the thiocyanate ion in urine samples.